Биофизическое взаимодействие света с биотканями - Коваль, Галина Юрьевна; Коваль, Г. В.; Солдатов, Анатолий Николаевич; Прокопьев, Владимир Егорович (Инноватика-2021 : сборник материалов XVII Международной школы-конференции студентов, аспирантов и молодых ученых, 22-23 апреля 2021 г., г. Томск, Россия)
The possibilities of modern oncology have significantly expanded with the advent of photodynamic therapy (PDT). Photodynamic therapy is a fundamentally new method of treating malignant neoplasms based on the use of photodynamic damage to tumor cells during a photochemical reaction.